Research on the quality hospice care of elderly cancer patients in China under social work intervention - Li Wang; Zhizhong Wang (Komiyama Printing Co. Ltd, 2020)
Abstract Background Few studies have specifically addressed quality of life issues for elderly hospice patients. The purpose of this study is to explore various factors and service patterns of the quality of life of end-of-life care for the elderly. Methods We collect the data and make small-scale exploratory study via semi-structured individual interviews. Data were collected from the family of 2 elderly cancer patients receiving hospice services, and the data were analyzed qualitatively. Results After investigation, we found that elderly people in hospice care, regardless of age, are suffering from physical and psychological pain and do not want to spend the rest of their lives in the hospital, but want to die in their own homes. Conclusions Both hospitalization and in-home care can improve resource utilization, and the key is to find various factors affecting the quality of life. Improving the quality of life is what patients and their families need most.